Lithium iron phosphate positive electrode material, preparation method thereof and electrochemical device

Through multi-step preparation methods, including sand grinding, spray drying, sintering and particle size grading, the problems of low energy density and complex preparation process of lithium iron phosphate positive electrode materials are solved, and materials with high energy density and high compaction density are achieved, which is suitable for industrial production.

CN119660701APending Publication Date: 2025-03-21NANTONG RESHINE NEW MATERIAL CO LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411918601.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The low energy density of lithium iron phosphate cathode material limits its application in the power battery market, and the existing preparation process is complex and the compaction density is low.

Method used

High compaction and high capacity lithium iron phosphate positive electrode material is prepared by a multi-step preparation method including first sanding, spray drying, sintering, second sanding and resintering. This method improves the electrochemical properties and compaction density of the material through particle size grading and the use of coating agents.

Benefits of technology

It realizes the preparation of high energy density lithium iron phosphate positive electrode materials at lower sintering temperatures, simplifies the process flow, reduces costs, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660701A_ABST
    Figure CN119660701A_ABST
Patent Text Reader

Abstract

The invention provides a lithium iron phosphate positive electrode material, a preparation method thereof and an electrochemical device, and the preparation method comprises the following steps: adding a first carbon source, a lithium source, an iron source and a phosphorus source into water, and carrying out first sanding to obtain a first mixture; carrying out spray drying treatment on the first mixture, and sintering in inert gas to obtain a precursor; mixing the precursor, a second carbon source and water to obtain a second mixture; sanding the second mixture for the second time, and dividing the second mixture into a first slurry and a second slurry when the particle size D50 of the second mixture is 1.0-2.0 [mu] m; carrying out third sanding on the second slurry, wherein the particle size D50 of the sanded second slurry is 0.2-0.3 [mu] m; mixing the first slurry and the second slurry subjected to third sanding to obtain mixed slurry; and carrying out spray drying treatment on the mixed slurry, and sintering in inert gas to obtain the lithium iron phosphate positive electrode material. According to the preparation method of the lithium iron phosphate positive electrode material provided by the invention, the compaction density and the electrical property of the lithium iron phosphate positive electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy, and specifically to a lithium iron phosphate positive electrode material and a preparation method and an electrochemical device thereof. Background Art

[0002] Lithium iron phosphate cathode material is one of the most widely used battery systems in electric vehicles and energy storage due to its advantages such as good safety, low cost, stable structure and long cycle life. However, its low energy density limits its share in the power battery market. Therefore, it is of great significance to improve the energy density of lithium iron phosphate.

[0003] At present, the industry's process for preparing and producing lithium iron phosphate positive electrode materials is complex, and the compaction density of lithium iron phosphate positive electrode materials is relatively low, which needs to be further improved. Summary of the invention

[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a method for preparing a lithium iron phosphate positive electrode material.

[0005] In addition, the embodiments of the present application also provide a lithium iron phosphate positive electrode material prepared by the aforementioned preparation method and an electrochemical device using the lithium iron phosphate positive electrode material.

[0006] The embodiment of the present application provides a method for preparing a lithium iron phosphate positive electrode material, comprising: adding a first carbon source, a lithium source, an iron source, and a phosphorus source into water, and performing a first sand milling to obtain a first mixture; spray drying the first mixture to obtain a first material; sintering the first material under an inert gas to obtain a precursor; mixing the precursor, a second carbon source, and water to obtain a second mixture; sand milling the second mixture for a second time, and when the particle size D50 of the second mixture is 1.0 μm to 2.0 μm, dividing the second mixture into a first slurry and a second slurry; sand milling the second slurry for a third time, and the particle size D50 of the second slurry after the third sand milling is 0.2 μm to 0.3 μm; mixing the first slurry and the second slurry after the third sand milling to obtain a mixed slurry; spray drying the mixed slurry to obtain a second material; sintering the second material under an inert gas to obtain the lithium iron phosphate positive electrode material.

[0007] In some possible implementations, in the mixed slurry, the mass ratio of the first slurry to the second slurry is 1:(1-2.5).

[0008] In some possible implementations, in the first mixture, the mass of the phosphorus source is a, and the mass of the first carbon source is (3.5%~6%)*a.

[0009] In some possible implementations, after the first sanding, the particle size D50 of the first mixture is 1.0 μm to 1.35 μm.

[0010] In some possible implementations, the sintering temperature of the first material is 600° C. to 750° C., and the sintering time is 7 h to 12 h, or / and the sintering temperature of the second material is 700° C. to 800° C., and the sintering time is 3 h to 15 h.

[0011] In some possible implementations, a coating agent is further added to the second mixture, and the coating agent includes at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide or niobium pentoxide.

[0012] In some possible implementations, based on the mass of the second mixture, the mass of the coating agent is 0.1% to 0.3% of the mass of the precursor.

[0013] In some possible implementations, based on the mass of the second mixture, the mass of the second carbon source is 3.5% to 6% of the mass of the precursor.

[0014] The present application also provides a lithium iron phosphate positive electrode material, which is prepared by the aforementioned method for preparing the lithium iron phosphate positive electrode material.

[0015] The present application also provides an electrochemical device, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes the aforementioned lithium iron phosphate positive electrode material.

[0016] In the preparation method provided in the present application, a single crystal lithium iron phosphate precursor of a single sintering is prepared through a single treatment and a single sintering process, and in a secondary treatment process, particles with different particle sizes D50 are obtained by sand-milling the second slurry again, and the particle size gradation of the sand-milled slurry is achieved by mixing large and small particle precursors, and a high-density and high-capacity lithium iron phosphate positive electrode material is prepared at a lower sintering temperature. The solution provided by the present invention has low requirements for raw materials, simple process, low cost, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of the crystalline lithium iron phosphate precursor prepared in Example 1.

[0018] Figure 2 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0019] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0020] The present application provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps: S1. Adding a first carbon source, a lithium source, an iron source, and a phosphorus source into water, and performing a first sand grinding to obtain a first mixture.

[0021] In this step, specifically, pure water is first added to the stirring tank, and during the stirring process, the first carbon source, lithium source, iron source, and phosphorus source are added in sequence. After sufficient stirring, the stirring speed is 300-600rpm / min, the stirring and dispersion time is not less than 60min, and the solid content is less than 60%, and then sand milling is performed, and the sand milling speed is 1000-1200rpm / min, and the sand milling is sand milled to a suitable particle size range. In some embodiments, the solid content of the first mixture can be 40%, 45%, 50%, 55%, 60% or any value between any two of the above numerical ranges. In some embodiments, the stirring speed can be 300 rpm / min, 400rpm / min, 500rpm / min, 600rpm / min or any value between any two of the above numerical ranges. In some embodiments, the sand milling speed is 1000rpm / min, 1100rpm / min, 1150rpm / min, 1200rpm / min or any value between any two of the above numerical ranges.

[0022] The molar ratio of Li:Fe:P in the lithium source, iron source and phosphorus source is (1.0-1.03):1:(1.015-1.036). The above ratio is conducive to obtaining a lithium iron phosphate positive electrode material with higher purity. In some embodiments, the molar ratio of Li:Fe:P is 1:1:1.015, 1:1:1.036, 1.01:1:1.036, 1.03:1:1.015, 1:1:1.025, 1:1:1.030, etc.

[0023] In some embodiments, in the first mixture, the mass of the phosphorus source is a, and the mass of the first carbon source is (3.5%~6%)*a. In the subsequent sintering process, the first carbon source acts as a reducing agent to inhibit the oxidation of divalent iron and improve the reduction of iron. The mass of the first carbon source within the above range is conducive to improving the purity of the precursor prepared during the sintering process. If the mass of the first carbon source is less than 3.5%*a, the content of the first carbon source is small, which will affect the reduction of iron and thus affect the subsequent formation of crystalline lithium iron phosphate; if the mass of the first carbon source is greater than 6%*a, the content of the first carbon source is large, and the purity of the prepared crystalline lithium iron phosphate is not high, thereby affecting the subsequent formation of crystalline lithium iron phosphate. In some embodiments, the mass of the first carbon source is 3.5%*a, 4%*a, 4.5%*a, 4.8%*a, 5%*a, 5.2%*a, 5.5%*a, 6%*a or any value between any two of the above numerical ranges.

[0024] In some embodiments, the phosphorus source is a mixture of any one or more of ferric phosphate, phosphoric acid, lithium dihydrogen phosphate, and monoammonium phosphate. The iron source is a mixture of any one or more of ferric phosphate, ferric oxide, ferric oxide, and ferric hydroxide. The lithium source is a mixture of any one or more of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate. The first carbon source is any one or more of glucose, sucrose, citric acid, polyethylene glycol, cyclodextrin, polyvinyl alcohol, phenolic resin, polyacrylonitrile, starch, and cellulose.

[0025] In some embodiments, after the first sanding, the particle size D50 of the first mixture is 1.0 μm to 1.35 μm. The particle size D50 of the first mixture is within the above range, which improves the uniformity of the particle size in the first mixture, and is also conducive to improving the reactivity of the first mixture particles in the subsequent sintering, and improving the reaction rate. The particle size D50 of the first mixture can be 1.0 μm, 1.05 μm, 1.1 μm, 1.15 μm, 1.2 μm, 1.25 μm, 1.3 μm, 1.35 μm or any value between any two of the above ranges.

[0026] S2. Processing the first mixed material by spray drying to obtain a first material.

[0027] In the spray drying process, the inlet air temperature of the spray drying is 220°C to 240°C, and the outlet air temperature of the spray drying is 95°C to 100°C. The first mixed material is subjected to the above-mentioned spray drying granulation to obtain a material with uniform particle size. The first mixed material is fully granulated at the above-mentioned inlet air temperature and outlet air temperature, and the granulation rate is increased. The inlet air temperature can be 220°C, 230°C, 240°C, etc., and the outlet air temperature can be 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, etc.

[0028] S3. Under an inert gas, sinter the first material to obtain a precursor.

[0029] In this step, the first material is sintered to obtain a lithium iron phosphate precursor.

[0030] In some embodiments, the temperature for sintering the first material is 600°C to 750°C, and the sintering time is 7h to 12h. At this sintering temperature, the first material is fully sintered to form a crystalline lithium iron phosphate precursor. If the sintering temperature is less than 600°C, the sintering temperature is low, which is not conducive to the formation of a crystalline lithium iron phosphate precursor; if the sintering temperature is greater than 750°C, the temperature is too high, which will cause the prepared precursor to harden, and the hardness is too high, which is not conducive to subsequent grinding applications. In some embodiments, the sintering temperature can be 600°C, 620°C, 650°C, 680°C, 700°C, 750°C or any value between any two of the above numerical ranges. The sintering time of the first material is within the above range, so that there is sufficient sintering time at a suitable sintering temperature to obtain a lithium iron phosphate precursor with higher purity. In some embodiments, the sintering time can be 7h, 8h, 9h, 10h, 11h, 12h or any value between any two of the above numerical ranges.

[0031] In some embodiments, the inert gas includes at least one of nitrogen, argon, and helium, which helps prevent oxidation of the lithium iron phosphate precursor, thereby improving its crystallinity.

[0032] S4. Mixing the precursor, the second carbon source and water to obtain a second mixture.

[0033] In this process, the solid content of the second mixture is less than 60%, such as 40%, 45%, 50%, 55%, etc. In the subsequent sintering process, the second carbon source in the second mixture forms a coating layer on the surface of the lithium iron phosphate positive electrode material, controls the particle size of the lithium iron phosphate positive electrode material, and is beneficial to improving the electrochemical performance of the lithium iron phosphate positive electrode material.

[0034] In some embodiments, the second carbon source comprises at least one of glucose, sucrose, citric acid, polyethylene glycol, cyclodextrin, polyvinyl alcohol, phenolic resin, polyacrylonitrile, starch, and cellulose.

[0035] In some embodiments, a coating agent is further added to the second mixed material, and the coating agent includes at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide or niobium pentoxide. The addition of the above coating agent is conducive to improving the electrochemical performance, structural stability, thermal stability and other properties of the lithium iron phosphate positive electrode material, and improving the comprehensive performance of the lithium iron phosphate positive electrode material.

[0036] S5. The second mixture is sand-milled for a second time, and when the particle size D50 of the second mixture is 1.0 μm to 2.0 μm, the second mixture is divided into a first slurry and a second slurry; the second slurry is sand-milled for a third time, and the particle size D50 of the second slurry after the third sand-milling is 0.2 μm to 0.3 μm.

[0037] In this step, when the particle size D50 of the second mixture is 1.0 μm to 2.0 μm, it is beneficial to improve the uniformity of the reaction of the second mixture slurry in the subsequent sintering, and within this range, it is also beneficial to further improve the compaction density of the positive electrode material when the lithium iron phosphate positive electrode material has a good capacity, and reduce the grinding cost. The particle size D50 of the second slurry after the third sand grinding is within the above range. The particle size D50 of the second slurry is further ground to make its particle size smaller than the particle size D50 of the first slurry. The particles in the dried second slurry can be fully filled in the gaps between the particles of the dried first slurry. This combination of large particles and small particles can fully improve the compaction density of the lithium iron phosphate positive electrode material, thereby improving the energy density of the lithium-ion battery.

[0038] In some embodiments, the particle size D50 of the first slurry may be 1.0 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, or any value between any two of the above numerical ranges.

[0039] In some embodiments, the particle size D50 of the second slurry after the third sanding may be 0.2 μm, 0.21 μm, 0.23 μm, 0.25 μm, 0.28 μm, 0.3 μm or any value between any two of the above numerical ranges.

[0040] S6. Mix the first slurry and the second slurry after the third sand grinding, and stir to obtain a mixed slurry.

[0041] In some embodiments, in the mixed slurry, the mass ratio of the first slurry to the second slurry is 1:(1-2.5). Within this range, while the subsequently prepared lithium iron phosphate positive electrode material can have a good capacity, the particles in the second slurry after the third sand grinding can be fully filled in the gaps between the particles of the first slurry, so that the first slurry and the second slurry are fully mixed to further improve the compaction density of the lithium iron phosphate positive electrode material.

[0042] In some embodiments, in the mixed slurry, the mass ratio of the first slurry to the second slurry may be 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.3, 1:2.5, or the like.

[0043] In some embodiments, the first slurry and the second slurry are stirred for more than 1 hour after mixing, and the stirring speed is 300-600 rpm / min, so that the first slurry and the second slurry are fully mixed, which is conducive to improving the uniformity of subsequent sintering. In some embodiments, the stirring speed can be 300 rpm / min, 400 rpm / min, 500 rpm / min, 600 rpm / min, or any value between any two of the above numerical ranges.

[0044] S7. Drying the mixed slurry by spray drying to obtain a second material.

[0045] In the spray drying process, the inlet air temperature of the spray drying is 220°C to 240°C, and the outlet air temperature of the spray drying is 95°C to 100°C. The second material is granulated by the above-mentioned spray drying to obtain a material with uniform particle size. The second material is fully granulated at the above-mentioned inlet air temperature and outlet air temperature, and the granulation rate is increased to increase the volatilization rate and drying degree of the liquid medium and impurities. The inlet air temperature can be 220°C, 230°C, 240°C, etc., and the outlet air temperature can be 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, etc.

[0046] S8. Under an inert gas, sinter the second material to obtain a lithium iron phosphate positive electrode material.

[0047] After the second material is sintered for the second time, it is then subjected to airflow crushing, screening and iron removal to obtain a lithium iron phosphate positive electrode material. The sintered second material can be carbon-coated on the basis of the lithium iron phosphate precursor to improve the conductivity of the lithium iron phosphate positive electrode material, and can also improve the crystallinity of the lithium iron phosphate positive electrode material, thereby improving the problem of abnormal growth of primary particles that may occur in the sintering or sand milling process of the first material; in addition, it can also improve the stability of the lithium iron phosphate positive electrode material and reduce the risk of poor stability of the lithium iron phosphate positive electrode material due to poor stability of the raw iron source and phosphorus source. This step can effectively control the size distribution of the lithium iron phosphate positive electrode material particles, reduce crystal defects, and improve overall performance.

[0048] In some embodiments, the second material is sintered at a temperature of 700° C. to 800° C., and the sintering time is 3 h to 15 h.

[0049] At this sintering temperature, the second material is fully sintered to form crystalline lithium iron phosphate. In some embodiments, the temperature for sintering the second material can be 700°C, 720°C, 750°C, 780°C, 800°C or any value between any two of the above numerical ranges. The sintering time of the second material is within the above range, so that there is sufficient sintering time at a suitable sintering temperature to obtain lithium iron phosphate with higher purity. In some embodiments, the sintering time can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or any value between any two of the above numerical ranges.

[0050] In some embodiments, the heating rate of sintering the second material can be 2°C / min~5°C / min to 700°C to 800°C, which is conducive to uniform heating, avoiding excessive thermal stress, and preventing agglomeration caused by rapid heating. The heating rate can further be 3°C / min~5°C / min, and can be exemplarily 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min or any value between any two of the above numerical ranges.

[0051] In some embodiments, the inert gas includes at least one of nitrogen, argon, and helium, which helps prevent oxidation of the lithium iron phosphate positive electrode material, thereby improving its crystallinity.

[0052] In the preparation method provided by the present application, a single crystal lithium iron phosphate precursor of a single sintering is prepared through a single treatment and a single sintering process. In the secondary treatment process, particles with different particle sizes D50 are obtained by sand-milling the second slurry again, and the particle size gradation of the sand-milled slurry is achieved by mixing large and small particle precursors, and a high-density and high-capacity lithium iron phosphate positive electrode material is prepared at a lower sintering temperature. The solution provided by the present application has low requirements for raw materials, simple process, and low cost, and is suitable for large-scale industrial production.

[0053] The embodiment of the present application also provides a lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material is prepared by the above-mentioned preparation method of the lithium iron phosphate positive electrode material, has good electrochemical properties and compaction density, and has low cost.

[0054] The present application also provides an electrochemical device (such as a battery), which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet includes the lithium iron phosphate positive electrode material. The electrochemical device includes a positive electrode sheet, and the positive electrode sheet contains a high-density, high-capacity lithium iron phosphate positive electrode material, which is conducive to improving the energy density, power density, charge and discharge efficiency, thermal stability and other properties of the electrochemical device.

[0055] The above-mentioned lithium iron phosphate positive electrode material and its preparation method are further described below through specific examples.

[0056] Example 1 (1) Preparation process of large-particle single-sintered lithium iron phosphate precursor Weigh lithium carbonate and iron phosphate respectively according to the raw material molar ratio of Li:Fe:P=1.025:1:1.03. Evenly mix 3.6kg starch, 25kg lithium carbonate, 100kg iron phosphate and 130kg water to obtain a mixture; The mixture was stirred at a stirring speed of 300-600 rpm / min for 90 min, and then introduced into a sand mill for sand grinding. The final grinding particle size D50 was 1.22 μm, thereby obtaining a first mixture.

[0057] The prepared first mixed material is spray-dried to obtain a first material, wherein the inlet air temperature of the spray-drying is 240° C. and the outlet air temperature is 100° C.

[0058] The spray-dried first material is sintered under nitrogen atmosphere protection conditions, raised to 700°C at a rate of 2.5°C / min, kept warm for 7.5 hours, and finally cooled. The cooled material is mechanically crushed to obtain a powdered crystalline lithium iron phosphate precursor.

[0059] (2) Preparation of lithium iron phosphate positive electrode material 100 kg of the crystalline lithium iron phosphate precursor prepared in step (1), 3.5 kg of glucose, and 6.0 kg of polyethylene glycol were mixed with 100 kg of water at a stirring speed of 300-600 rpm / min for 90 min to obtain a second mixture.

[0060] The second mixed material was introduced into a sand mill for grinding. When the particle size was D50 = 1.55 μm, 159.5 kg of slurry (first slurry) was taken out, and the remaining slurry (second slurry) was further sand milled. Finally, the particle size of the second slurry was D50 = 0.26 μm.

[0061] The first slurry and the second slurry were mixed in a weight ratio of 1:1, and stirred for 90 minutes at a stirring speed of 300-600 rpm / min to obtain a mixed slurry.

[0062] The prepared mixed slurry is spray dried and granulated to obtain a second material, wherein the spray drying air inlet temperature is set to 240°C and the air outlet temperature is set to 100°C.

[0063] The dried second material is sintered under nitrogen protection conditions, the temperature is raised to 780°C at a rate of 2.5°C / min, kept warm for 7.5 hours, and finally cooled to obtain a sintered product. The sintered product of the secondary sintering is subjected to air flow crushing, sieving, and iron removal to obtain a lithium iron phosphate positive electrode material.

[0064] Example 2 The difference between Example 2 and Example 1 is that "the first slurry and the second slurry are mixed in a weight ratio of 1:1" is replaced by "the first slurry and the second slurry are mixed in a weight ratio of 1:1.5", and the other steps are the same as Example 1.

[0065] Example 3 The difference between Example 3 and Example 1 is that "the first slurry and the second slurry are mixed in a weight ratio of 1:1" is replaced by "the first slurry and the second slurry are mixed in a weight ratio of 1:2.5, and the other steps are the same as Example 1.

[0066] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the first slurry and the second slurry are not mixed, and only the second slurry is used for spray drying, and the other steps are the same as Example 1.

[0067] Relevant tests were performed on the lithium iron phosphate positive electrode materials prepared in the above embodiment and comparative example.

[0068] Specific surface area: Using the nitrogen adsorption-desorption method, at liquid nitrogen temperature, the equilibrium adsorption amount of nitrogen on the surface of an object is related to its specific surface area and other characteristics. Combined with the law of change of adsorption amount with relative pressure during the adsorption process, the specific surface area test can be carried out.

[0069] Carbon content: The carbon content of lithium iron phosphate positive electrode material is tested by infrared analysis. The sample is burned in a high-temperature, oxygen-rich state using a carbon-sulfur analyzer. The carbon element it contains is oxidized into carbon dioxide and enters the infrared detector with the carrier gas. The carbon content is calculated by quantitatively analyzing the changes in the intensity of the infrared absorption wavelength of the carbon dioxide signal.

[0070] Powder compaction density: Tested with reference to the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals "Determination of compaction density of lithium-ion battery positive electrode material powder".

[0071] Powder resistivity test: Test according to the method specified in the standard drafted by the National Technical Committee for Standardization of Nonferrous Metals "Determination of Powder Resistivity of Lithium-ion Battery Positive Electrode Materials".

[0072] Electrical performance test: The lithium iron phosphate positive electrode materials in the embodiment and the comparative example were made into positive electrode sheets for button-type battery assembly, and metallic lithium was used as the negative electrode material. The assembled button-type battery was tested within the voltage range of 2.0~3.75V.

[0073] The test steps for the first charge and discharge efficiency include: at a normal temperature of 25°C, charge the lithium-ion battery at a constant current of 0.1C to 3.75V, then charge at a constant voltage until the current drops to 0.05C, stop charging, and record the first charge capacity; then discharge at 0.1C to a cut-off voltage of 2.0V, record the first discharge capacity, calculate the 0.1C specific capacity of the positive electrode material based on the first discharge capacity, and calculate the first charge and discharge efficiency of the battery, i.e., the first efficiency, according to the following formula: first charge and discharge efficiency = (first discharge capacity / first charge capacity) * 100%.

[0074] Then repeat the above charge and discharge process once at 1C current, record the 2nd charge capacity and 2nd discharge capacity, and calculate the 1C specific capacity of the positive electrode material with the 2nd discharge capacity.

[0075] Table 1 Comparison of performance data of the embodiments and comparative examples In the above Table 1, the positive electrode materials of Example 1, Example 2, Example 3 and the comparative example were subjected to physicochemical index and electrochemical tests respectively. In Example 1 to Example 3, as the ratio of the first slurry to the second slurry in the small-particle primary sintered lithium iron phosphate precursor increased (1:1, 1:1.5 and 1:2.5, respectively), the powder compaction density of the lithium iron phosphate positive electrode material gradually decreased from 2.65 to 2.58 and 2.55, and the 0.1C gram capacity of the button battery increased from 157.1mAh / g to 158.7 and 159.3mAh / g. This is due to the increase of the small particle slurry of the second slurry, which in turn led to a decrease in the powder compaction density and an improvement in the electrical performance of the button battery. Compared with Comparative Example 1, the compaction of the lithium iron phosphate positive electrode materials prepared in Examples 1 to 3 is greatly improved.

[0076] See also Figure 1 , Figure 1 This is a scanning electron microscope image of the crystalline lithium iron phosphate precursor prepared in Example 1. The particles of the lithium iron phosphate precursor are evenly distributed and the particle sizes are similar. Figure 2 , Figure 2 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material prepared in Example 1. Before spray drying, the particle size of the first slurry and the second slurry are graded. The particle size grading of large and small particles in the lithium iron phosphate positive electrode material is beneficial to improving the compaction density of the lithium iron phosphate positive electrode material.

[0077] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: include: Adding a first carbon source, a lithium source, an iron source, and a phosphorus source into water, and performing a first sand grinding to obtain a first mixture; Treating the first mixed material by spray drying to obtain a first material; Sintering the first material under an inert gas to obtain a precursor; Mixing the precursor, a second carbon source and water to obtain a second mixture; performing a second sand grinding on the second mixture, and when the particle size D50 of the second mixture is 1.0 μm to 2.0 μm, dividing the second mixture into a first slurry and a second slurry; Performing a third sand grinding on the second slurry, wherein the particle size D50 of the second slurry after the third sand grinding is 0.2 μm to 0.3 μm; Mixing the first slurry and the second slurry after the third sand grinding to obtain a mixed slurry; Treating the mixed slurry by spray drying to obtain a second material; The second material is sintered under an inert gas to obtain the lithium iron phosphate positive electrode material.

2. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the mixed slurry, the mass ratio of the first slurry to the second slurry is 1:(1-2.5).

3. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: In the first mixture, the mass of the phosphorus source is a, and the mass of the first carbon source is (3.5%-6%)*a.

4. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: After the first sanding, the particle size D50 of the first mixture is 1.0 μm to 1.35 μm.

5. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The temperature of sintering the first material is 600° C. to 750° C., and the sintering time is 7 h to 12 h, or / and The temperature for sintering the second material is between 700° C. and 800° C., and the sintering time is between 3 h and 15 h.

6. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: A coating agent is further added to the second mixture, and the coating agent includes at least one of titanium dioxide, tetrabutyl titanate, magnesium oxide, magnesium acetate, magnesium hydroxide, magnesium nitrate, zirconium nitrate, zirconium hydroxide, zirconium oxide or niobium pentoxide.

7. The method for preparing the lithium iron phosphate positive electrode material according to claim 6, characterized in that: Based on the mass of the second mixture, the mass of the coating agent is 0.1% to 0.3% of the mass of the precursor.

8. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: Based on the mass of the second mixture, the mass of the second carbon source is 3.5% to 6% of the mass of the precursor.

9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 8.

10. An electrochemical device, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode sheet comprises the lithium iron phosphate positive electrode material as claimed in claim 9.

Citation Information

Cited By

  • Low-impurity phosphate positive electrode material and preparation method thereof, positive electrode and lithium secondary battery

    CN120504306A

  • Low-impurity phosphate-based positive electrode material, preparation method thereof, positive electrode, and lithium secondary battery

    CN120504306B

  • High-compaction lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN120841472A